Efektivitas Model Pembelajaran Gerak Manipulatif Melempar Pada Siswa Sekolah Dasar - Abyudaya, Aristawati Amoret; Sari, Eka Fitri Novita; Sukriadi, Slamet (Prodi Pendidikan Jasmani dan Olahraga, 2025)
Manipulative movement is one of the basic movements that elementary school students must know, understand and master. There are 3 basic manipulative movements that must be mastered by elementary school students, namely throwing, catching, and kicking. Throwing is the main focus in this research. 6 game learning models divided into 6 posts based on 6 modified learning media throwing using 6 learning media namely 3 media balls with different weights, used paper, 1 media ball made of cloth, and 1 cube. This study uses the action research method of ADDIE development methodology and uses observation and interview analysis techniques. The results of the development of learning models and learning media are that students have increased by 70% at SDN 02 and 76% at SDN 06 which can be seen from the implementation of pre tests and post tests with 3 treatments after the pre test.